Teacher’s Oral Feedback in Speaking Activity at the Tenth Grade of Senior High School - Nurul Azmi; Ariatna Ariatna (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2026)
This study aimed to identify the types of teacher oral feedback strategies used during speaking activities and to describe their implementation at the tenth grade of MAN Pematangsiantar. This study employed a descriptive qualitative research design. The data were collected through classroom observation, supported by video recording, audio recording, and field notes, involving one English teacher and thirty-six students of grade tenth. The data were analyzed using the oral corrective feedback framework proposed by Ellis (2009) and the learner error categories proposed by Lyster and Ranta (1997), as adapted by Faris (2018). The qualitative data were analyzed through the procedures proposed by Miles, et al. (2014). The findings revealed that the teacher used four out of six oral feedback strategies, namely recast, clarification request, explicit correction, and elicitation. Recast was the most frequently used strategy (45.4%), followed by clarification request (27.2%), explicit correction (18.1%), and elicitation (9.09%). Repetition and paralinguistic signal were not observed during the classroom interactions. Furthermore, the implementation of oral feedback was triggered by four types of learner errors, namely grammar errors, vocabulary errors, pronunciation errors, and L1 use. Grammar and pronunciation errors were the most frequently occurring errors.